Reading Manna and Quail in the Exodus: A Reader Response Criticism Perspective - Gulo, Eirene; Taogan, Frischo Ridhoi (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
Reader Response Criticism is a postmodernist interpretation approach. The spirit of postmodernism greatly influences the interpretive activities carried out by this method. The philosophy of postmodernism is apparent in the characteristics of reader response criticism. The author explains how the Reader Response Criticism approach works in this study. In the research framework, the author uses the literature study method to obtain research data and the biblical hermeneutic method to find news from the Bible. From this research, it can be concluded that Reader Response Criticism considers that manna comes from several proposals, both animals and plants, which tells that the event did not happen miraculously but something normal based on the availability of manna in the area, as well as the quails they came usually because of fatigue so that no visible action of God in the event. But biblically speaking, both of these events were God working miraculously to do His providence for the Israelites who had been freed from slavery and had to pass through the wilderness for 40 years, and God provided food for them.